Quantitative Content Analysis of Library Websites of State and Foundation Universities in Türkiye - Toprak, Fatma; Çapkın, Çağdaş (Information World, 2025)
This study aims to conduct a content analysis of the library websites of state and foundation universities in Türkiye based on current items, to assess Türkiye’s position at an international level, and to offer suggestions for improvement. Within the scope of the research, a total of 206 university library websites were examined, including 128 state and 78 foundation universities. Quantitative content analysis was conducted using a checklist of 88 items under nine headings derived from the literature. The research data were analyzed quantitatively using relationship (Chi-square and correlation) and mean or median comparison (independent sample t-test and Mann-Whitney U) tests. The results indicated that state universities had a significantly higher mean number of items (41) compared to foundation universities (35), that there was a weak negative correlation between the university’s foundation year and content diversity (r = -0.202), and that 29 items showed a relationship with the university type. Comparisons with international studies showed that university library websites in Türkiye provide less than 50% coverage in 29 items, primarily Web 2.0 tools, mobile applications, user guides, in-site search, site maps, information literacy programs and feedback, and show lower performance compared to both developed and some developing countries in these items. Research results can guide university libraries in developing digital service policies and library managers and webmasters in technological adaptation processes.
Keywords: University libraries; library services; library websites; website content; web content analysis